Polycarbonate blends with high environmental stress crack resistance, high strength and high toughness by introducing polyvinyl butyral at small fraction. (1st March 2022) - Xu, Haoyu; Yang, Jianing; Zhang, Xuhui; Li, Ting; Huang, Jing; Chen, Mingqing; Dong, Weifu
Abstract: It is of great importance to prepare polycarbonate (PC) with high environmental stress crack resistance (ESCR), high strength and high toughness by melting blend. In this work, by incorporating small fraction of PVB, a commercial available engineering plastics with excellent flexibility at high temperature, PC/PVB blends with obviously improved ESCR are obtained. The enhanced ESCR is mainly ascribed to the decreased internal stress due to the low Tg and flexibility of PVB. On one hand, the low Tg and flexibility make PVB deformable during cooling to release the tension force of PC which results from the different cooling rate between surface and internal. On the other hand, the low Tg and flexibility of PVB can promote the motion of PC chains and decrease the viscosity of PC fusant to weaken the orientation force. Besides, without adding any compatibilizer, PC/PVB blends well maintain the high strength and toughness of PC due to the uniform dispersion of PVB and excellent mechanical properties of PVB at room temperature. We envision that this work offers an alternative facile method to prepare PC blends with high environmental stress crack resistance, high strength and high toughness and will promote the wide application of PC. Graphical abstract: By adding polyvinyl butyrate (PVB), a polyhydroxy engineering polymer with flexibility, PC/PVB blends exhibit an obviously improved environmental stress cracking resistance, while maintaining the excellent mechanical properties of PC without adding any compatibilizer. This work provides a facile method for preparing PC with excellent comprehensive performance, and will further expand the application range of PC. Image 1 Highlights: By melt blending, PVB can disperse uniformly in PC. PVB can effectively decrease the internal force of PC at small fraction. PC/PVB blends show an obviously improved ESCR and good mechanical properties.